Electron beam hybrid welding-brazing of WC-Co/40Cr dissimilar materials. Issue 6 (15th April 2019) - Chen, Guoqing; Shu, Xi; Liu, Junpeng; Zhang, Bo; Zhang, Binggang; Feng, Jicai
Abstract: A novel electron beam hybrid welding method is proposed in this paper. A brazing weld was achieved by heat conduction while electron beam welding was conducted. The annular fusion joint of a WC-Co cemented carbide head and 40Cr steel pedestal was obtained to ensure an effective connection with high strength. At the same time, a brazing joint was formed between the bottom surfaces of WC-Co and 40Cr steel by heat conduction, guaranteeing heat dissipation during working. The results showed that the carbon-poor environment was easily formed at the WC-Co/weld interface in the fusion weld. Excellent electron beam welding-brazing joints were obtained with no macro cracks or pores in the fusion weld, and effective bonds in the brazing weld were achieved by a defocusing treatment. The brazing weld mainly consisted of solder and base metal indrafted from the molten pool. The brazing seam generated from the molten solder was mainly composed of Cu-Ti compound, Ag-Cu eutectic phase and a small amount of Ni-Ti and Co-Ti compounds, with Cu-Ti compound segregation at the interface of the brazing seam. The maximum shear strength and micro hardness of the fusion weld reached 586 MPa and HV812, respectively.